The Analysis of Pb Content in Tilapia Fish from Taliwang Lake - Khairuddin, Khairuddin; Yamin, M.; Kusmiyati, Kusmiyati (Jurnal Biologi Tropis, 2025)
Research on the heavy metal lead (Pb) is important to protect consumers from dangerous heavy metal contamination. The main objective of this research is to determine the levels of Lead (Pb) metal in the body of Tilapia Fish (Oreochromis mossambicus) obtained in Taliwang Lake. The results of this study are useful so that consumers of Tilapia fish can avoid fish that are contaminated with Pb heavy metals. Data collection for this research was carried out in Taliwang Lake. It was determined that there were 2 stations in this research, namely in the eastern and western parts of the lake. Fish were caught by using gill nets. Four fish were taken at each research station as samples. The next stage, the Tilapia fish samples were wrapped in plastic samples, which were then placed in sample boxes. The destruction of tilapia fish muscle samples was carried out in the Mataram University Analytical Laboratory and the Pb content analysis was carried out at the DLHK Environmental Laboratory West Nusa Tenggara. The Pb metal content was analyzed by using an AAS (Atomic Absorption Spectrophotometer) tool. Measurement of this heavy metal was carried out by adding concentrated HNO3 and HClO4 then heated at a temperature of 60 - 70ºC with a time span of 2-3 hours until the solution became clear. The solution sample was then measured with an AAS tool using an air-acetylene flame. The conclusion of this research was that the content of heavy metal Lead (Pb) in the tissue of Tilapia Fish (Oreochromis mossambicus) taken from Lake Taliwang waters was 0.0005 mg/kg (ppm).